SAE Technical Paper Series 2009
DOI: 10.4271/2009-01-2624
|View full text |Cite
|
Sign up to set email alerts
|

Autoignition Characteristics of Primary Reference Fuels and their Mixtures

Abstract: This study investigates the autoignition of Primary Reference Fuels (PRFs) using a detailed kinetic model. The chemical kinetics software CHEMKIN is used to facilitate solutions in a constant volume reactor and a variable volume reactor, with the latter representing an IC engine. Experimental shock tube and HCCI engine data from literature is compared with the present predictions in these two reactors. The model is then used to conduct a parametric study in the constant volume reactor of the effect of inlet pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The higher energy release from richer mixtures during the first stage ignition speeds up the reactions leading up to the second stage ignition, resulting in shorter overall ignition delay times. Sjöberg and Dec [33] observed experimentally an increase in cool flame activity with increasing ϕ for PRF 60 and PRF 80, and Little et al [34] demonstrated computationally an increase in first stage heat release with richer fuel-air mixtures for PRF 20. The ability of the ignition delay predictions for varying ϕ to replicate the trends observed experimentally in the literature lends credence to the methodology adopted in this study in terms of incorporating the effects of equivalence ratio into the "TRF 91" ignition delay correlation.…”
Section: Effect Of Fuel-air Equivalence Ratio On Autoignitionmentioning
confidence: 98%
“…The higher energy release from richer mixtures during the first stage ignition speeds up the reactions leading up to the second stage ignition, resulting in shorter overall ignition delay times. Sjöberg and Dec [33] observed experimentally an increase in cool flame activity with increasing ϕ for PRF 60 and PRF 80, and Little et al [34] demonstrated computationally an increase in first stage heat release with richer fuel-air mixtures for PRF 20. The ability of the ignition delay predictions for varying ϕ to replicate the trends observed experimentally in the literature lends credence to the methodology adopted in this study in terms of incorporating the effects of equivalence ratio into the "TRF 91" ignition delay correlation.…”
Section: Effect Of Fuel-air Equivalence Ratio On Autoignitionmentioning
confidence: 98%